Sensing high concentrations in air of H2 based on spin-coated films of flame-spray-made SnO2 and Pd/SnO2 nanoparticles - Chaikarn Liewhiran (2018)
Flame Spray Pyrolysis (FSP) was performed for the synthesis of high specific surface area (SSABET) of SnO2 nanopowders (141.6 m2/g) and supported palladium (Pd) nanoparticles containing 0.2-3 wt%Pd with controlled size and a crystallinity in a single step. The particles properties were further characterized by XRD, BET and TEM analyses. The crystalline particles were used for sensing film preparation by spin coating. It was found that the flame-spray-made 0.2 wt%Pd/SnO2 sensor showed higher and faster response to reducing H2 gas than pure flame-spray-made SnO2 sensor. © (2010) Trans Tech Publications.